Effects of intensive agriculture in the structure and functioning of tropical headwater streams - Taniwaki, Ricardo Hideo (2016)
Tropical regions hold the planet´s most biodiverse ecosystems. Despite its importance to biodiversity and conservation, anthropogenic activities are degrading these ecosystems, with unknown consequences for its functioning and structure. In between the several ecosystems through the tropics, freshwater ecosystems call attention, due to its small fraction of area comparing to terrestrial ecosystems, that represent an enormous importance for human surviving and developing. Headwater streams constitute the majority of water bodies in a catchment, and therefore, it is essential for the health of the entire freshwater ecosystems. Several headwater streams are inserted in agricultural lands, suffering from the pressures from agricultural intensification. Therefore, this thesis was developed aiming to understand what are the main pressures that tropical headwater streams has been suffering, worldwide and locally in the Corumbataí river basin. The first chapter will contribute to understanding what are the main issues that tropical streams have been experiencing, focusing on agricultural multiple stressors and climate change effects. The second chapter analyzes how the conversion of low-intensity pasturelands to high-intensity bioenergy crops changes the water quality parameters in streams located in the Corumbataí river basin and also examines how important are the riparian forests in the headwater zone to provide better water quality in bioenergy crops. The third chapter investigates how water quality and climatic characteristics affect benthic biofilm community dynamics in tropical headwater streams in the Corumbataí river basin. The results have shown the existence of several knowledge gaps about tropical streams, mainly related to the effects of climate change, multiple stressors and the lack of policies and mitigation strategies for climate change. In relation to water quality, we found that the conversion of low-intensity pastures to high-intensity bioenergy crops are degrading water quality. Riparian forests in the springhead zone have demonstrated to be essential in providing water quality in bioenergy crops, especially in the wet season. The benthic biofilm community seems to be controlled mainly by climate characteristics and not by nutrient availability as observed in temperate streams. Therefore, a climate change scenario, the benthic biofilm will be strongly affected, with consequences in the functioning of tropical headwater streams. To reduce the negative impacts of intensive agriculture and climate change, we recommend the implementation of riparian forests, with special attention to the springhead area and also the implementation of best agricultural practices in tropical agriculture to ensure the sustainability of tropical freshwater resources.